Obtention of blue colorant from jenipapo fruit - Renhe, Isis Rodrigues Toledo; Stringheta, Paulo César; Silva, Fabyano Fonseca e; Oliveira, Taíla Veloso de (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to evaluate the influence of solvents with different pH and temperatures over the color quality of blue colorant extracted from jenipapo fruit (Genipa americana). The green fruit was triturated with water and with alcohol solution at 50 and 95% concentration with previously adjusted pH (4, 5, 6, 7, 8, and 9) and heated (35, 45, 55, 65, and 75°C). The extracts were compared to an indigotin standard for color measurement. Temperature and pH affected the extraction, and the optimum results were achieved at pH 4 and 75°C temperature for alcohol solvents and at 55°C for water.